Human-forest relationship in the Budapest agglomeration: an urban-rural divide among forest visitors - Hafenscher, Priszcilla; Kukely, György; Bárdi, Árpád János; Bazsó-Bertalan, Laura; Papp-Vancsó, Judit; Jankó, Ferenc (Hungarian Geographical Bulletin, 2025)
This paper conducted 1000n survey comprising 27 questions at five urban and semi-natural sample sites to analyse the human-forest relationship in Budapest and its suburban areas. The study examines the relationship between the respondent residence types – the urban-rural divide – forest use, human-nature connectedness (HNC), environment-related well-being, and activities categorized under pro-environmental behaviour (PEB). The present study employed statistical analysis with the R statistical program. The results revealed significant differences between respondents living in Budapest, suburban areas, and rural areas. Budapest residents and suburban dwellers spend less time visiting forests but hold more positive views of Hungary’s environmental status. People living in Budapest also had a significantly lower nature dependency score determined by living conditions (-) and education (+). Moreover, pro-environmental habits were slightly higher among city dwellers but lower among suburban newcomers. Education levels also proved to be a more significant variable in determining whether respondents supported green policies. A further finding indicates surveys conducted in natural settings may also influence and fortify respondents’ forest valuation, HNC, and PEB.